PEMANFAATAN LIMBAH IKAN DAN SISA MAKANAN UNTUK PELET PAKAN IKAN DI WISATA DELTA FISHING SIDOARJO - Siska Desti Rahayu; Demes Nurmayanti; Fitri Rokhmalia (Poltekkes Kemenkes Surabaya, 2016)
Delta Fishing is a fishing ponds and family recreation areas located in Sidoarjo Regency. Activities at Delta Fishing generate untreated fish wastes and food leftovers, leading to problems such as odor around the site. The purpose of this study was to utilize fish wastes and leftovers* for fish feed pellets in Delta Fishing of Sidoarjo Regency. This study was a pre-experiment using the posttest-only design. Objects were subjected to several treatments and pretests by utilizing the fish wastes and leftovers as raw materials for the manufacture of fish feed pellets for gouramis of 5-15 cm in size. Each sample treatment was replicated 5 times and subjected to laboratory tests to determine the contents of protein in the fish pellets. Results showed that the fish pellets made from fish wastes had an average protein content of 59.2% and those made from leftovers had 32%. There was a difference in the average protein content of pellets made from fish wastes and those made from leftovers with a p-value of (0.000 0.05). Conclusion of this study, fish pellets with good protein contents derived from leftovers with a protein content of 32%, in contrast to those made from fish wastes with a protein content of 59.2%. The management of Delta Fishing is recommended to use the findings of the present study to evaluate and solve waste generation that may lead to the inconvenience of visitors and residents around Delta Fishing. Keywords : Fish wastes and leftovers, fish pellets.